Xerostomia: Development of a candy with potential sialogogue - Dalmagro, Maristela Fátima (2015)
Xerostomia, known as dry mouth, may be a consequence or not of the decline and of the interruption of the salivary glands with reduced salivary flow and the consequences of which could compromise the nutritional status and health of the individu- al. The purpose of this study was to develop a jelly candy plus functional and sialogogues ingredients. Three candies formu- lations were developed with tangerine, strawberry and mint fla- vors. There were sensory analysis by applying the Acceptance Test with hedonic scale of nine points, ranging from disliked very much to liked very much, considering the attributes: appearance, taste, texture, aroma and microbiological and physical-chemical analysis. The analyzed samples have been adapted to Brazilian legislation on microbiological parame- ters. This physical-chemical analysis revealed that the candies with 308 kcal / 100 g, and 18.26 g / 100 g of protein. As for the sensory analysis appearance and texture attributes showed no difference among the candies, however the aroma and flavor attributes were significantly different and strawberry flavor candy was preferred by 104 people untrained panel. The results suggest that the candy can be beneficial, innovative and well - accepted by patients with xerostomia, but clinical studies to evaluate this effect are still needed.